2003
DOI: 10.1111/1468-2389.00224
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Dimensionality of Counterproductive Work Behavior

Abstract: The study investigated the dimensionality of counterproductive work behavior (CWB) by examining the relationships between various counterproductive behaviors. Utilizing a university alumni sample (N = 343), data was collected through both self–report and direct judgments of the likelihood of co–occurrence. Eleven categories of CWB were examined: (1) Theft and Related Behavior; (2) Destruction of Property; (3) Misuse of Information; (4) Misuse of Time and Resources; (5) Unsafe Behavior; (6) Poor Attendance; (7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
406
1
21

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 509 publications
(436 citation statements)
references
References 33 publications
8
406
1
21
Order By: Relevance
“…Counterproductive Work Behavior (CWB): An 84-item questionnaire was used in this study to measure counterproductive work behavior. The items in this section are mostly based on the questionnaire used by Gruys and Sackett (2003), but some items were also added. The original questionnaire contained 63 items, and so for the purpose of analysis only these items will be included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Counterproductive Work Behavior (CWB): An 84-item questionnaire was used in this study to measure counterproductive work behavior. The items in this section are mostly based on the questionnaire used by Gruys and Sackett (2003), but some items were also added. The original questionnaire contained 63 items, and so for the purpose of analysis only these items will be included.…”
Section: Methodsmentioning
confidence: 99%
“…In 2000, Bennett and Robinson revisited their categorization and suggested that CWB be categorized into two general dimensions of interpersonal deviance and organizational deviance. Gruys and Sackett (2003) proposed a more comprehensive model that comprises of eleven categories of CWB: theft and related behavior, destruction of property, misuse of information, misuse of time and resources, unsafe behavior, poor attendance, poor quality work, alcohol use, drug use, inappropriate verbal actions, and inappropriate physical actions. Spector et al (2006) suggested that CWB be looked at as having five categories of abuse, theft, withdrawal, production deviance, and sabotage.…”
Section: Introductionmentioning
confidence: 99%
“…In essence, teachers are also normal individuals, hence exhibits similar behaviors as of the typical employees (Bayram, Gursakal, & Bilgel, 2009). Nevertheless, CWB is still considered quite harmful to both the people working within and to the organization itself (Gruys & Sackett, 2003;Robinson & Bennett, 1995;Sackett, 2002). Therefore, in order to prevent the current situation from getting worst, it is quite important to truly understand and determine the various CWBs that are currently happening inside the school.…”
Section: Introductionmentioning
confidence: 99%
“…Withdrawal was measured with the items from ste study of Gruys and Sackett (2003). Using a response format ranging from 1 (never) to 5 (always), we asked participants to indicate the frequency with which they behaved as such.…”
Section: Participants and Proceduresmentioning
confidence: 99%